Proton exchange membrane and proton exchange membrane coated with catalyst
By introducing an enhanced membrane structure, a continuous non-porous H2 recombination catalyst coating, and a cross-linked polyelectrolyte multilayer coating into the proton exchange membrane, the high cost and safety issues in proton exchange membrane water electrolysis technology have been solved, achieving high-purity hydrogen production and improved cost-effectiveness.
Patent Information
- Application Number
- CN202480041165.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-23
- Filing Date
- 2024-06-17
- Publication Date
- 2026-01-16
AI Technical Summary
Existing proton exchange membrane water electrolysis technology suffers from high capital costs, expensive precious metal catalysts, and hydrogen permeability and safety issues. In particular, the AEMWE system suffers from insufficient membrane hydroxide ion conductivity and stability, leading to high costs and potential safety hazards.
An enhanced membrane structure is adopted, combining a continuous non-porous H2 recombination catalyst coating and a continuous non-porous cross-linked polyelectrolyte multilayer coating. The coating contains hydrogen recombination catalyst and proton-conducting ionomer, which form a cross-linked polyelectrolyte multilayer through layer-by-layer self-assembly, thereby improving the mechanical strength and chemical stability of the membrane and reducing hydrogen permeability.
It significantly improves the purity of hydrogen production, reduces the hydrogen content in the anode oxygen, solves safety issues, and lowers production costs by using cheaper catalysts and materials, while improving mechanical strength and proton conductivity.
Smart Images

Figure CN121358894A_ABST
Abstract
Description
Priority Statement
[0001] This application claims priority to U.S. Nonprovisional Patent Application Serial No. 18 / 585,222, filed February 23, 2024, which claims priority to U.S. Provisional Patent Application Serial No. 63 / 509,806, filed June 23, 2023, the entire contents of which are incorporated herein by reference. Background Technology
[0002] Hydrogen plays a crucial role in the transition to an environmentally friendly, low-carbon energy structure, serving as an energy carrier for grid balancing or in power-to-gas and power-to-liquid processes. Water electrolysis produces high-quality hydrogen by electrochemically breaking down water into hydrogen and oxygen; this reaction is given by Equation 1. Water electrolysis is an endothermic process, and electricity is the energy source. When the process is powered by renewable energy sources such as wind, solar, or geothermal energy, water electrolysis has a zero carbon footprint. Major water electrolysis technologies include alkaline electrolysis, proton exchange membrane (PEM) water electrolysis (such as... Figure 1 The PEMWE shown), anion exchange membrane (AEM) water electrolysis (such as Figure 2 The AEMWE shown is a solid oxide water electrolysis.
[0003] like Figure 1 As shown, in the PEMWE system 100, the anode 105 and the cathode 110 are separated by a solid PEM electrolyte 115, such as that labeled Nafion. ® A fluorinated copolymer based on sulfonated tetrafluoroethylene, sold by Chemours company. The anode and cathode catalysts typically consist of IrO2 and Pt, respectively. At the positively charged anode 105, pure water 120 is oxidized to produce oxygen 125 and electrons (e). - The reaction is given by Equation 2. Protons are transported from the anode 105 to the cathode 110 via the proton-conducting PEM 115. At the negatively charged cathode 110, a reduction reaction occurs, in which electrons from the cathode 110 are donated to protons to form hydrogen gas 130; this reaction is given by Equation 3. The PEM 115 not only conducts protons from the anode 105 to the cathode 110, but also separates the H2 gas 130 and O2 gas 125 produced in the water electrolysis reaction. PEM water electrolysis is one of the advantageous methods for converting renewable energy into high-purity hydrogen gas, with advantages such as high pressure differential, high current density, high efficiency, fast response, small footprint, low temperature (20°C–90°C) operation, and compact system design with high-purity oxygen byproducts. However, one of the main challenges of PEM water electrolysis is the high capital cost of the battery stack, including expensive acid-resistant stack hardware (such as Pt-coated Ti bipolar plates), expensive precious metal catalysts required for the electrodes, and expensive PEM.
[0004] Water electrolysis reaction: 2 H2O → 2 H2 + O2 (1)
[0005] The anodizing reaction of PEMWE: 2 H₂O → O₂ + 4 H₂ + + 4 e - (2)
[0006] The cathodic reduction reaction of PEMWE: 2 H + + 2 e- → H2(3)
[0007] AEMWE is a developing technology. For example... Figure 2 As shown, in the AEMWE system 200, the anode 205 and cathode 210 are separated by a solid AEM electrolyte 215. Typically, a water feed 220 with an added electrolyte (such as diluted KOH or K₂CO₃ or deionized water) is fed to the cathode side. In some cases, the water feed 220 with an added electrolyte (such as diluted KOH or K₂CO₃ or deionized water) is fed to the anode side or both the cathode and anode sides. The anode and cathode catalysts typically comprise Ni-based or Ni alloy catalysts that do not contain platinum group metals. At the negatively charged cathode 210, water is reduced to form hydrogen 225 and hydroxide ions by adding four electrons; this reaction is given by Equation 4. The hydroxide ions diffuse from the cathode 210 to the anode 205 via the AEM 215, which conducts the hydroxide ions. At the positively charged anode 205, the hydroxide ions recombine to form water and oxygen 230; this reaction is given by Equation 5. AEM 215 not only conducts hydroxide ions from cathode 210 to anode 205, but also separates H2 225 and O2 230 generated in the water electrolysis reaction. AEM 215 allows the production of hydrogen 225 with a very high purity of at least 99.9% under high pressures up to 35 bar.
[0008] AEMWE's cathodic reduction reaction:
[0009] 4 H2O + 4 e - →2 H2 + 4 OH - (4)
[0010] AEMWE's anodizing reaction:
[0011] 4 OH - →2 H₂O + O₂ + 4 e⁻ - (5)
[0012] AEMWE has advantages over PEMWE in that it allows the use of cheaper catalysts that do not contain platinum group metals, such as Ni and Ni alloy catalysts. In addition, much cheaper stainless steel bipolar plates can be used in the gas diffusion layers (GDLs) of AEMWE, instead of the expensive Pt-coated Ti bipolar plates currently used in PEMWE. However, the biggest obstacles to developing AEM systems are membrane hydroxide ion conductivity and stability, and lack of understanding of how to integrate catalysts into AEM systems. Research on AEMWE in the literature has focused on developing electrocatalysts, AEMs, and understanding the operating mechanisms, with the general goal of obtaining a high- efficiency, low-cost, and stable AEMWE technology.
[0013] An anode in an electrochemical cell is an electrode in which the primary reaction is oxidation (e.g., water oxidation / oxygen evolution reaction electrode for a water electrolyzer). A cathode in an electrochemical cell is an electrode in which the primary reaction is reduction (e.g., proton reduction / hydrogen evolution reaction electrode for a water electrolyzer).
[0014] Membranes are one of the key materials that make up an electrolyzer and are an important driver of safety and performance. Some important properties of membranes for electrolysis include high conductivity, high ion permeability, high ion exchange capacity (for ion exchange membranes), high ion / H2 and O2 selectivity (low H2 and O2 permeability / crossover), low price, low area resistance that minimizes efficiency loss due to ohmic polarization, high resistance to oxidation and reduction conditions, chemical inertness over a wide pH range, high thermal stability, and high proton conductivity and high mechanical strength (thickness, low swelling).
[0015] More recently, newer cost-effective high-performance membrane materials have been invented for use with cell stack components for water electrolysis that have broad applications in renewable energy systems. While presumably effective for their intended purpose, hydrogen gas is known to be able to migrate through thin films and affect the effectiveness and efficiency of the cell. If the concentration of H2 in O2 reaches 2%, H2 crossover from the cathode stream to the anode stream also causes safety issues.
[0016] Accordingly, it would be desirable to provide a low-cost, easy-to-manufacture membrane that reduces or eliminates the amount of hydrogen gas that flows through the membrane. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 is an illustration of one embodiment of a PEMWE cell.
[0018] Figure 2 is an illustration of one embodiment of an AEMWE cell.
[0019] Figure 3 is an illustration of one embodiment of a proton exchange membrane of the present invention, which includes a reinforced membrane that includes a single layer membrane for PEMWE applications.
[0020] Figure 4 is an illustration of one embodiment of a proton exchange membrane of the present invention, which includes a reinforced membrane comprising a multi-layer membrane for PEMWE applications.
[0021] Figure 5 is a graph of polarization curves at 80 °C, atmospheric pressure, for a water electrolyzer comprising: (a) PEM-RHPE-CCM and (b) N115-CCM. DETAILED DESCRIPTION
[0022] The present invention relates to a novel proton exchange membrane and a method of making the same. The proton exchange membrane can be used to make a catalyst-coated membrane for water electrolysis to produce green H2.
[0023] The proton exchange membrane includes a reinforced membrane (e.g., less than or equal to 100 pm), a continuous non-porous H2recombination catalyst coating, and a continuous non-porous cross-linked polyelectrolyte multilayer coating. A free radical scavenger can be included in the H2recombination catalyst coating to improve the chemical / electrochemical stability of the membrane. The continuous non-porous cross-linked polyelectrolyte multilayer coating is disposed on the continuous non-porous H2recombination catalyst coating. Both the continuous non-porous cross-linked polyelectrolyte multilayer coating and the continuous non-porous H2recombination catalyst coating are water insoluble. The continuous non-porous cross-linked polyelectrolyte multilayer coating and the H2recombination catalyst coating significantly reduce the permeation of hydrogen gas from the cathode side to the anode side through the reinforced membrane, which results in higher gas purity. It also addresses the safety issue compared to proton exchange membranes without the continuous non-porous H2recombination catalyst coating and the continuous non-porous cross-linked polyelectrolyte multilayer. The proton exchange membrane in combination with the reinforced membrane (single or multi-layer) provides significant improvement in hydrogen production rate and mechanical strength compared to non-reinforced membranes. By incorporating the H2recombination catalyst coating, the hydrogen content in the oxygen content at the anode of the water electrolyzer can be significantly reduced. The permeated hydrogen and oxygen form water at the H2recombination catalyst coating, resulting in higher gas purity and addressing the safety issue. The free radical scavenger (when present) improves the chemical / electrochemical stability of the proton exchange membrane.
[0024] One aspect of the present invention can be broadly characterized as a proton exchange membrane having: a reinforced membrane; a continuous non-porous H2recombination catalyst coating coated on a first surface of the reinforced membrane; and a continuous non-porous cross-linked polyelectrolyte multilayer coating disposed on the continuous non-porous H2recombination catalyst coating.
[0025] The reinforced membrane includes a reinforcing material and a proton-conducting ionomer. The reinforced membrane can be a single layer membrane as shown in Figure 3 or a multi-layer membrane as shown in Figure 4The multi-layer membrane is shown. The single-layer membrane includes a first reinforcing material and a first proton-conducting ionomer. The multi-layer membrane includes at least one reinforced layer and at least one unreinforced layer. The at least one reinforced layer includes a second reinforcing material and a second proton-conducting ionomer, and the at least one unreinforced layer includes a third proton-conducting ionomer. The second proton-conducting ionomer and the third proton-conducting ionomer can be the same or different.
[0026] Any suitable reinforcing material can be used. Suitable reinforcing materials include, but are not limited to, polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), polyether ether ketone (PEEK), polyimide (PI), polyetherimide (PEI), polybenzoxazole (PBO), polybenzimidazole (PBI), polysulfone (PSF), polyethersulfone (PES), aromatic polyamide, polypropylene (PP), polyethylene (PE), co-PP-PE, or combinations thereof.
[0027] Any suitable proton-conducting ionomer can be used in the reinforcing membrane. Suitable proton-conducting ionomers include, but are not limited to, a cation exchange polymer or a mixture of a cation exchange polymer and an inorganic filler that includes covalently bonded acidic functional groups. The cation exchange polymer includes a -SO3 - , -COO - , -PO3 2- , or -PO3H - cation exchange functional group. The cation exchange polymer can be selected from, but is not limited to, a perfluorinated ionomer, such as Nafion ® , Aciplex ® , and Aquivion ® , a cross-linked perfluorinated cation exchange polymer, a partially fluorinated cation exchange polymer, a cross-linked partially fluorinated cation exchange polymer, a non-fluorinated hydrocarbon polymer, a cross-linked non-fluorinated hydrocarbon cation exchange polymer, or combinations thereof.
[0028] The total thickness of the reinforced film (single layer or multiple layers) is 100 pm or less, for example, less than or equal to 100 pm, or less than or equal to 95 pm, or less than or equal to 90 pm, or less than or equal to 85 pm, or less than or equal to 80 pm, or less than or equal to 75 pm, or less than or equal to 70 pm, or less than or equal to 65 pm, or less than or equal to 60 pm, or less than or equal to 55 pm, or less than or equal to 50 pm, or less than or equal to 45 pm, or less than or equal to 40 pm, or less than or equal to 35 pm, or less than or equal to 30 pm, or less than or equal to 25 pm, or less than or equal to 20 pm, or less than or equal to 15 pm, or in the range of 10 pm to 100 pm, or 10 pm to 95 pm, or 10 pm to 90 pm, or 10 pm to 85 pm, or 10 pm to 80 pm, or 10 pm to 75 pm, or 10 pm to 70 pm, or 10 pm to 65 pm, or 10 pm to 60 pm, or 10 pm to 55 pm, or 10 pm to 50 pm, or 10 pm to 45 pm, or 10 pm to 40 pm, or 10 pm to 35 pm, or 10 pm to 30 pm, or 10 pm to 25 pm, or 10 pm to 20 pm, or 10 pm to 15 pm.
[0029] The continuous non-porous H2recombination catalyst coating includes a mixture of a hydrogen (H2) recombination catalyst and a proton-conducting ionomer. Any suitable hydrogen recombination catalyst can be used. Suitable hydrogen recombination catalysts include, but are not limited to, Pt, Pt supported on carbon or silica, PtCo, PtCo supported on carbon or silica, Pd, Pd supported on carbon or silica, PdCo, PdCo supported on carbon or silica, or mixtures thereof.
[0030] The weight ratio of hydrogen recombination catalyst to proton-conducting ionomer in the continuous non-porous H2recombination catalyst coating is in the range of 1 :500 to 1 :20, or 1 :200 to 1 :50, or 1 : 100 to 1 :50.
[0031] The thickness of the continuous non-porous H2recombination catalyst coating is typically in the range of 1 micrometer to 50 micrometers, or 1 micrometer to 45 micrometers, or 1 micrometer to 40 micrometers, or 1 micrometer to 35 micrometers, or 1 micrometer to 30 micrometers, or 1 micrometer to 25 micrometers, or 1 micrometer to 20 micrometers, or 1 micrometer to 15 micrometers, or 5 micrometers to 50 micrometers, or 5 micrometers to 45 micrometers, or 5 micrometers to 40 micrometers, or 5 micrometers to 35 micrometers, or 5 micrometers to 30 micrometers, or 5 micrometers to 25 micrometers, or 5 micrometers to 20 micrometers, or 5 micrometers to 15 micrometers, or 10 micrometers to 50 micrometers, or 10 micrometers to 45 micrometers, or 10 micrometers to 40 micrometers, or 10 micrometers to 35 micrometers, or 10 micrometers to 30 micrometers, or 10 micrometers to 25 micrometers, or 10 micrometers to 20 micrometers, or 10 micrometers to 15 micrometers.
[0032] The H2recombination catalyst coating can optionally include a radical scavenger to improve the chemical / electrochemical stability of the proton exchange membrane. The radical scavenger can include, but is not limited to, inorganic nanoparticles including Ce02, Ce(OH)4, Ce02 / Zr02, Ce(OH)4 / Zr02, Zr02, silica gel, precipitated silica, fumed silica, colloidal silica, or mixtures thereof. The inorganic nanoparticles have a size in the range of 1 nanometer to 500 nanometers, or 1 nanometer to 400 nanometers, or 1 nanometer to 300 nanometers, or 1 nanometer to 250 nanometers, or 1 nanometer to 200 nanometers, or 1 nanometer to 150 nanometers, or 1 nanometer to 100 nanometers, or 1 nanometer to 50 nanometers, or 5 nanometers to 500 nanometers, or 5 nanometers to 400 nanometers, or 5 nanometers to 300 nanometers, or 5 nanometers to 250 nanometers, or 5 nanometers to 200 nanometers, or 5 nanometers to 150 nanometers, or 5 nanometers to 100 nanometers, or 5 nanometers to 50 nanometers, or 10 nanometers to 500 nanometers, or 11 nanometers to 400 nanometers, or 10 nanometers to 300 nanometers, or 10 nanometers to 250 nanometers, or 10 nanometers to 200 nanometers, or 10 nanometers to 150 nanometers, or 10 nanometers to 100 nanometers, or 10 nanometers to 50 nanometers.
[0033] The proton-conducting ionomer in the continuous non-porous H2recombination catalyst coating includes a proton-conducting ionomer or cross-linked proton-conducting ionomer that includes repeating units of both electrically neutral repeating units and a portion of ionized functional groups, such as -SO3 − , -COO - , -PO3 2− , -PO3H − , -C6H4O - , or -O4B - . The proton-conducting ionomer contains a high water-affinity polar or charged functional group, such as -SO3 − , -COO- or -PO3 2− Group.
[0034] In this invention, proton-conducting ionomers, cation-exchange polymers, and proton-exchange polymers are interchangeable.
[0035] Suitable proton-conducting ionomers include, but are not limited to, cation exchange polymers or mixtures of cation exchange polymers with inorganic fillers comprising covalently bonded acidic functional groups. Cation exchange polymers include negatively charged -SO3 groups. - -COO - -PO3 2- or -PO3H - Cation exchange functional group. The cation exchange polymer can be selected from, but is not limited to, perfluorinated ionomers, such as Nafion. ® Aciplex ® and Aquivion ® Cross-linked perfluorinated cation exchange polymers, partially fluorinated cation exchange polymers, cross-linked partially fluorinated cation exchange polymers, nonfluorinated hydrocarbon polymers, cross-linked nonfluorinated hydrocarbon cation exchange polymers, or combinations thereof.
[0036] The cation exchange polymer can be a perfluorinated sulfonic acid-based polymer, a perfluorinated carboxylic acid polymer, a sulfonated aromatic polymer, a crosslinked sulfonated aromatic polymer, or a combination thereof. The cation exchange polymer can be a copolymer of tetrafluoroethylene and perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-5-oxa-6-heptene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-4-oxa-5-hexene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-3-oxa-4-pentene-sulfonic acid, a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2- methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2-methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2-methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2-methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and 2,2,4-trifluoro-5- trifluoromethoxy-l,3-dioxolene, a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and 2,2,4- trifluoro-5-trifluoromethoxy-l,3-dioxolene, a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-l,3-dioxolene, a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-l,3-dioxolene, sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(ether sulfone), sulfonated poly(phenyl sulfone), sulfonated poly(2,6-dimethyl-l,4-phenylene oxide), sulfonated poly(4-phenoxybenzoyl-l,4- phenylene), sulfonated poly(phenylene ether), sulfonated poly(phenylene), sulfonated poly(phthalazinone), crosslinked SPEEK, crosslinked sulfonated poly(ether sulfone), crosslinked sulfonated poly(phenyl sulfone), crosslinked poly(phenylene sulfide sulfone nitrile), sulfonated polystyrene, sulfonated poly(vinyltoluene), crosslinked sulfonated polystyrene, crosslinked sulfonated poly(vinyltoluene), or a combination thereof.
[0037] The reinforced membrane (single or multiple layers) includes a cation exchange polymer or a mixture of a cation exchange polymer and an inorganic filler that includes covalently bonded acidic functional groups. The cation exchange polymer can include -SO3 - , -COO - , -PO3 2- , or -PO3H - cation exchange functional groups. The cation exchange polymer can be selected from, but not limited to, a perfluorinated ionomer such as Nafion ® , Aciplex ® , or Aquivion ® , a crosslinked perfluorinated cation exchange polymer, a partially fluorinated polymer, a crosslinked partially fluorinated proton exchange polymer, a non-fluorinated hydrocarbon polymer, a crosslinked non-fluorinated hydrocarbon proton exchange polymer, or a combination thereof. The reinforced proton exchange membrane single or multiple layers have high mechanical strength, good chemical and thermal stability, and good proton conductivity.
[0038] The reinforced membrane including a single layer membrane can be the composite proton conductive membrane described in U.S. Patent Application No. 17 / 162,421, filed January 29, 2021, entitled “Composite Proton Conductive Membranes,” which is incorporated by reference herein in its entirety. This application discloses a novel composite proton conductive membrane that includes an inorganic filler having covalently bonded acidic functional groups and a high surface area of at least 150 m 2 / g, and a water insoluble ion conducting polymer. The deposition of the polyelectrolyte multilayer coating on the composite proton conductive membrane results in reduced membrane swelling, significantly reduced H2 and O2 crossover, and enhanced proton conductivity compared to the composite proton conductive membrane without the polyelectrolyte multilayer coating.
[0039] The inorganic filler including covalently bonded acidic functional groups in the reinforced proton exchange membrane single or multiple layers can be selected from, but not limited to, silica gel, precipitated silica, fumed silica, colloidal silica, alumina, silica-alumina, zirconia, molecular sieve, metal organic framework, zeolitic imidazolate framework, covalent organic framework, or a combination thereof, and wherein the filler can have covalently bonded acidic functional groups and a surface area of 150 m 2 / g or higher, or 300 m 2 / g or higher, or 400 m 2 / g or higher high surface area. The molecular sieve has a framework structure, which can be characterized by a unique wide-angle X-ray diffraction pattern. Zeolites are a subclass of molecular sieves based on silicoaluminate compositions. Non-zeolite molecular sieves are based on other compositions, such as aluminophosphates, silicoaluminophosphates, and silica. Molecular sieves can have different chemical compositions and different framework structures. The molecular sieve can be a microporous or mesoporous molecular sieve and needs to be stable in aqueous solutions with a pH less than 6. The acidic functional group covalently bonded to the inorganic filler can be selected from, but not limited to, -H2PO3, -R-H2PO3, -SO3H, -R-SO3H, -COOH, -R-COOH, -C6H5OH, -R-C6H5OH, or combinations thereof, where R represents a linear alkyl group, a branched alkyl group, a cyclic alkyl group, an organic amino group, an acid group-substituted organic amino group, or an aryl group, and the number of carbon atoms in these groups is preferably 1 to 20, more preferably 1 to 10. The inorganic filler can be, but is not limited to, in the form of particles, fine beads, thin plates, rods, or fibers. The size of the inorganic filler is in the range of 2 nm to 200 pm, or in the range of 10 nm to 100 pm, or in the range of 50 nm to 80 pm. In some embodiments, the inorganic filler is an aminopropyl-N,N-bis(methylphosphonic acid) functionalized silica gel such as Silica MetS ® AMPA, aminopropyl-N,N-bis(methylphosphonic acid) functionalized fumed silica, n-propylphosphonic acid functionalized silica gel, n-propylphosphonic acid functionalized fumed silica, p-toluenesulfonic acid functionalized silica gel, p-toluenesulfonic acid functionalized fumed silica, 4-ethylbenzenesulfonic acid functionalized silica gel such as Silica Bond ® methylbenzenesulfonic acid, 4-ethylbenzenesulfonic acid functionalized fumed silica, n-propylsulfonic acid functionalized silica gel, n-propylsulfonic acid functionalized fumed silica, or combinations thereof.
[0040] The continuous non-porous crosslinked polyelectrolyte multilayer coating includes alternating layers of polycationic polymer and polyanionic polymer. The polycationic polymer layer is deposited on and in contact with the continuous non-porous H2reforming catalyst coating. There can be one set, two sets, three sets, four sets, five sets, or more sets of alternating polycationic polymer layers and polyanionic polymer layers on the surface of the cation exchange membrane. The top layer of the polyelectrolyte multilayer coating can be a polycationic polymer layer or a polyanionic polymer layer.
[0041] The thickness of the polyelectrolyte multilayer coating is typically less than the thickness of the reinforced proton exchange membrane. The thickness of the polyelectrolyte multilayer coating is typically in the range of 1 nanometer to 200 nanometers, or 1 nanometer to 150 nanometers, or 1 nanometer to 100 nanometers, or 1 nanometer to 50 nanometers, or 1 nanometer to 20 nanometers, or 2 nanometers to 200 nanometers, or 2 nanometers to 150 nanometers, or 2 nanometers to 100 nanometers, or 2 nanometers to 50 nanometers, or 2 nanometers to 20 nanometers, or 5 nanometers to 200 nanometers, or 5 nanometers to 150 nanometers, or 5 nanometers to 100 nanometers, or 5 nanometers to 50 nanometers, or 5 nanometers to 20 nanometers.
[0042] A second polyelectrolyte multilayer coating can be present on the second surface of the reinforced membrane.
[0043] The polyelectrolyte multilayer coating can be formed using a layer-by-layer self-assembly method. For example, the layer-by-layer self-assembly can be achieved by adsorption, electrostatic interaction, covalent bond, hydrogen bond, van der Waals force, hydrophobic interaction, or a combination thereof. The method of forming the polyelectrolyte multilayer coating via layer-by-layer self-assembly can be selected from, but not limited to, dip coating, spray deposition, centrifugal deposition, electrodeposition, meniscus / slit die coating, brush coating, roller coating, metering bar / Meyer bar coating, knife casting, and the like.
[0044] The choice of the manufacturing method depends on the polycations and polyanions to be assembled, the time required for the layer-by-layer self-assembly, and the shape of the membrane on which the polyelectrolyte multilayer coating will be deposited. The first polyelectrolyte layer is formed by adsorbing, for example, a polycation or a polyanion on the surface of a continuous non-porous H2reforming catalyst coating. Subsequently, a second polyelectrolyte layer having a charge opposite to that of the first polyelectrolyte layer is deposited on the first polyelectrolyte layer to form a set of alternating layers on the continuous non-porous H2reforming catalyst coating. The increase in the thickness of the polyelectrolyte multilayer is dependent on the number of layers deposited and can be linear or non-linear. During the layer-by-layer self-assembly, several parameters can be adjusted, such as ionic strength, pH, temperature, polyelectrolyte structure, concentration, and charge density. Polyelectrolyte layers having opposite charges are deposited on the surface of the continuous non-porous H2reforming catalyst coating. The polyelectrolyte multilayer has an ionic cross-linked structure and is insoluble in water, and is thermally and chemically stable.
[0045] The first layer deposited on the surface of the continuous non-porous H2recombination catalyst coating (and the second surface of the enhanced proton exchange membrane, if present) should be a layer of polycationic polymer with positive ionic charges opposite to those on the continuous non-porous H2recombination catalyst coating (and the enhanced proton exchange membrane layer), which results in the formation of a stable coating via electrostatic interactions between the cationic exchange polymer on the surface of the continuous non-porous H2recombination catalyst coating and the polycation deposited on the surface of the continuous non-porous H2recombination catalyst coating as the first part of the first polyelectrolyte bilayer. A polyanion polymer with opposite charges is then deposited on the surface of the first polycationic polymer coating via electrostatic interactions to form the second part of the first polyelectrolyte bilayer. A polyelectrolyte multilayer of (polycation-polyanion) n can be formed in the same alternating deposition process. The thickness of each layer of polyanion or polycation is less than 50 nm, or less than 20 nm, or less than 10 nm, or less than 5 nm. The polyanion polymers in the polyelectrolyte multilayer have negative charges and can be the same as or different from the cationic exchange polymers in the continuous non-porous H2recombination catalyst coating and the enhanced proton exchange membrane single or multilayer, but the polyanion polymer cannot be the first polyelectrolyte layer deposited on the surface of the continuous non-porous H2recombination catalyst coating with negative charges. The polyanion polymers suitable for making the polyelectrolyte multilayer have similar or higher proton conductivity than the enhanced proton exchange membrane and have similar or lower H2and O2permeability than the enhanced proton exchange membrane. However, the polyanion polymers and the polycation polymers are soluble in aqueous solutions, which makes the membranes made from the polyanion polymers or the polyanion polymers unsuitable for water electrolyzer or fuel cell applications. Therefore, it is important to form the polyelectrolyte multilayer comprising ionically cross-linked alternating polycations and polyanions. The polyelectrolyte multilayer formed via layer-by-layer self-assembly is not only water-insoluble and thermally and chemically stable, but also has significantly reduced swelling and H2and O2cross-over, as well as enhanced proton conductivity compared to the enhanced proton exchange membrane for water electrolyzer or fuel cell applications.
[0046] Poly cationic polymers suitable for preparing polyelectrolyte multilayer coatings include, but are not limited to, protonated chitosan; amine-based linear, highly branched, or dendritic polycationic polymers selected from the group consisting of polybiguanide, quaternary ammonium polyethyleneimine, quaternary ammonium polypropyleneimine, quaternary ammonium polyamidoamine (PAMAM), poly( vinylamine hydrochloride) (PVH), poly(allylamine hydrochloride) (PAH), poly(amidoamine hydrochloride), poly(N-isopropylallylamine hydrochloride), poly(N-tert-butylallylamine hydrochloride), poly(N-1,2-dimethylpropylallylamine hydrochloride), poly(N-methylallylamine hydrochloride), poly(N,N-dimethylallylamine hydrochloride), poly(2-vinylpiperidine hydrochloride), poly(4-vinylpiperidine hydrochloride), poly(4-vinylpyridine hydrochloride), poly(diallyldimethylammonium chloride), poly(acrylamide-co-diallyldimethylammonium chloride), poly(diallyldimethylammonium hydrochloride), copolymer of 2-propen-1-amine hydrochloride and N-2-propenyl-2-propen-1-amine hydrochloride, poly(N-alkyl-4-vinylpyridinium) salts, polylysine, polyornithine, polyarginine, poly(ethylene oxide)-block-poly(vinylbenzyltrimethylammonium chloride), poly(ethylene oxide)-block-poly(l-lysine), poly(2-methacryloyloxyethylphosphocholine methacrylate)-block-poly(vinylbenzyltrimethylammonium chloride), poly[2-(dimethylamino)-ethyl methacrylate, poly[3-(dimethylamino)-propyl methacrylate], poly[2-(dimethylamino)-ethyl methacrylamide], poly[3-(dimethylamino)propyl methacrylamide], poly[2-(trimethylamino)ethyl methacrylate chloride], poly[2-(diethylamino)ethyl methacrylate], poly[2-(dimethylamino)ethyl acrylate], or combinations thereof.
[0047] Polyanionic polymers suitable for preparing the polyelectrolyte multilayer coating include, but are not limited to, sulfonated hydrocarbon polymers, poly(acrylic acid), poly(sodium phosphates), or negatively charged polysaccharide polyanionic polymers, or combinations thereof. Suitable sulfonated hydrocarbon polymers include, but are not limited to, sulfonated poly(ether ether ketone), sulfonated polyether sulfone, sulfonated polyphenyl sulfone, sulfonated poly(2,6-dimethyl-1,4-phenylene oxide), sulfonated poly(4-phenoxybenzoyl-1,4-phenylene), sulfonated polyphenylene ether, sulfonated poly(phenylene), sulfonated poly(phthalazinone), sulfonated polystyrene, sulfonated poly(vinyltoluene), poly(acrylic acid), poly(vinylsulfonic acid sodium salt), poly(sodium phosphate), or combinations thereof. Suitable negatively charged polysaccharide polyanionic polymers include, but are not limited to, sodium alginate, potassium alginate, calcium alginate, ammonium alginate, alginic acid, sodium hyaluronate, potassium hyaluronate, calcium hyaluronate, ammonium hyaluronate, hyaluronic acid, kappa-carrageenan, lambda-carrageenan, iota-carrageenan, carboxymethyl gellan gum, carboxymethyl gellan gum sodium, carboxymethyl gellan gum potassium, carboxymethyl gellan gum calcium, carboxymethyl gellan gum ammonium, carboxymethyl cellulose, carboxymethyl cellulose sodium, carboxymethyl cellulose potassium, carboxymethyl cellulose calcium, carboxymethyl cellulose ammonium, or combinations thereof.
[0048] Another aspect of the present application can be broadly characterized as a proton exchange membrane comprising: a reinforced membrane (single layer or multiple layers) having a first surface and a second surface; a continuous non-porous H2recombination catalyst coating having a first surface and a second surface, the first surface of the continuous non-porous H2recombination catalyst coating on the first surface of the reinforced membrane, the continuous non-porous H2recombination catalyst coating comprising a mixture of a H2recombination catalyst, a proton-conducting ionomer, and optionally a radical scavenger; and a continuous non-porous crosslinked polyelectrolyte multilayer coating on the second surface of the coating, the polyelectrolyte multilayer coating comprising alternating layers of a polycationic polymer and a polyanionic polymer, and wherein the polycationic polymer layer is in contact with the continuous non-porous H2recombination catalyst coating; an anode on the second surface of the continuous non-porous crosslinked polyelectrolyte multilayer coating; and a cathode on the second surface of the reinforced proton exchange membrane; or a cathode on the second surface of a second continuous non-porous crosslinked polyelectrolyte multilayer coating on the second surface of the reinforced proton exchange membrane.
[0049] Any suitable anode and cathode materials can be used. Suitable anodes include, but are not limited to, iridium, platinum, ruthenium, osmium, rhodium, palladium, tin, tungsten, vanadium, cobalt, silver, gold, copper, nickel, molybdenum, iron, chromium, alloys thereof, oxides thereof, carbides thereof, phosphides thereof, or combinations thereof. Suitable cathodes include, but are not limited to, platinum, ruthenium, osmium, rhodium, palladium, tin, tungsten, vanadium, cobalt, silver, gold, nickel, molybdenum, iron, copper, chromium, alloys thereof, oxides thereof, carbides thereof, phosphides thereof, or combinations thereof.
[0050] Another aspect of the application can be broadly characterized as providing a method for making a proton exchange membrane, the method comprising: applying a continuous non-porous H2recombination catalyst coating directly on a first surface of a reinforced membrane, the continuous non-porous H2recombination catalyst coating comprising a mixture of a H2recombination catalyst, a proton-conducting ionomer, and optionally a radical scavenger; and applying a continuous non-porous crosslinked polyelectrolyte multilayer coating directly on a surface of the continuous non-porous H2recombination catalyst coating, the polyelectrolyte multilayer coating comprising alternating layers of a polycationic polymer and a polyanionic polymer, wherein the polycationic polymer layers are in contact with the continuous non-porous H2recombination catalyst coating.
[0051] The method can comprise: applying a second continuous crosslinked polyelectrolyte multilayer coating directly on a second surface of the reinforced membrane, the polyelectrolyte multilayer coating comprising alternating layers of a polycationic polymer and a polyanionic polymer, wherein the polycationic polymer layers are in contact with the reinforced proton exchange membrane.
[0052] The method can further comprise: applying an anode on a second surface of the continuous non-porous crosslinked polyelectrolyte multilayer coating and applying a cathode to a second surface of the reinforced membrane; or applying an anode on a second surface of the continuous non-porous crosslinked polyelectrolyte multilayer coating, applying a second continuous non-porous crosslinked polyelectrolyte multilayer coating on a second surface of the reinforced membrane, and applying a cathode on a second surface of the second continuous non-porous crosslinked polyelectrolyte multilayer coating.
[0053] Figure 3 One embodiment of a catalyst-coated membrane 300 incorporating a proton exchange membrane 305 is shown. The proton exchange membrane 305 comprises a reinforced membrane 310, which comprises a single layer comprising a reinforcing material 315 and a proton-conducting ionomer 320.
[0054] A continuous non-porous H2recombination catalyst coating 325 is present on a surface of the reinforced membrane 310. The continuous non-porous H2recombination catalyst coating 325 comprises a mixture of a hydrogen recombination catalyst 330 and a proton-conducting ionomer 335.
[0055] A continuous non-porous crosslinked polyelectrolyte multilayer coating 340 is present on a surface of the continuous non-porous H2recombination catalyst coating 325. The continuous non-porous crosslinked polyelectrolyte multilayer coating 340 comprises alternating layers of a polycationic polymer and a polyanionic polymer, and the polycationic polymer layers are in contact with the continuous non-porous H2recombination catalyst coating 325. A second continuous non-porous crosslinked polyelectrolyte multilayer coating 345 can optionally be present on the opposite side of the reinforced membrane 310.
[0056] An anode 350 is in close proximity to the continuous non-porous crosslinked polyelectrolyte multilayer coating 340, and a cathode 355 is in close proximity to the second continuous non-porous crosslinked polyelectrolyte multilayer coating 345 (as shown) or to the reinforcing membrane 310 (if the second continuous non-porous crosslinked polyelectrolyte multilayer coating 345 is not present).
[0057] Figure 4 One embodiment of a catalyst-coated membrane 400 incorporating a proton exchange membrane 405 is shown. The proton exchange membrane 405 includes a multilayer membrane 401 that includes three alternating thin layers of a reinforcing membrane 420 and a non-reinforcing membrane 460. The thin layers of the reinforcing membrane 420 include a reinforcing material 415 and a proton-conducting ionomer 410. The thin layers of the non-reinforcing membrane 460 include the proton-conducting ionomer 410.
[0058] A continuous non-porous H2recombination catalyst coating 425 is present on a surface of the multilayer membrane 401. The continuous non-porous H2recombination catalyst coating 425 includes a mixture of a hydrogen gas recombination catalyst 430 and a proton-conducting ionomer 435. The continuous non-porous H2recombination catalyst coating 425 can be in contact with the thin layers of the reinforcing membrane 420, as shown, or can be in contact with the thin layers of the non-reinforcing membrane 460. Figure 4
[0059] A continuous non-porous crosslinked polyelectrolyte multilayer coating 440 is present on a surface of the continuous non-porous H2recombination catalyst coating 425. The continuous non-porous crosslinked polyelectrolyte multilayer coating 440 includes alternating layers of a polycationic polymer and a polyanionic polymer, and the polycationic polymer layers are in contact with the continuous non-porous H2recombination catalyst coating 425. A second continuous non-porous crosslinked polyelectrolyte multilayer coating 445 can optionally be present on the opposite side of the multilayer membrane 401.
[0060] An anode 450 is in close proximity to the continuous non-porous crosslinked polyelectrolyte multilayer coating 440, and a cathode 455 is in close proximity to the second continuous non-porous crosslinked polyelectrolyte multilayer coating 445 (as shown) or to the multilayer membrane 401 (if the second continuous non-porous crosslinked polyelectrolyte multilayer coating 445 is not present).
[0061] Example
[0062] Example 1 : Nafion®-enhanced ™ XL-based membranes, H2recombination layers, and polyelectrolyte coatings Manufacture of PEM-RHPE
[0063] A mixture of a nanoscale Ce02, platinum black catalyst, Nafion® ionomer suspension, water, and EtOH was sonicated in an ice bath to form a hydrogen gas recombination ink dispersion. A thin layer of the hydrogen gas recombination ink was applied to a reinforcing Nafion® membrane purchased from ™ Gore® using a Mayer rod coating method. The hydrogen gas recombination ink was prepared by mixing a nanoscale Ce02, platinum black catalyst, Nafion® ionomer suspension, water, and EtOH in a 1 : 1 : 1 : 1 : 1 ratio. ™ on one surface of the XL base membrane. The coated membrane was dried in an oven at 60 °C for 30 minutes to evaporate all solvents and to cure the hydrogen recombination layer. Then, the membrane was annealed at 100 °C for 1 hour to form a Pt / Ce02 / Nafion ™ coated Nafion ™ membrane. A poly(allylamine hydrochloride) (PAH) polycation solution was prepared by dissolving NaCl and PAH in deionized (DI) H20. A sulfonated poly(ether ether ketone) (SPEEK) polyanion aqueous solution was prepared by dissolving NaCl and SPEEK in DI H20 at 80 °C. The Pt / Ce02 / Nafion ™ coated Nafion ™ on the Pt / Ce02 / Nafion ™ composite coating was immersed in the PAH polycation solution for 5 minutes and the membrane was rinsed with DI H20 three times. The membrane was then immersed in the SPEEK polyanion solution for 5 minutes. The membrane was rinsed with DI H20 three times and one ionically cross-linked PAH / SPEEK polyelectrolyte bilayer was deposited on the surface of the Pt / Ce02 / Nafion ™ composite coating. The process was repeated to deposit 3 sets of PAH / SPEEK polyelectrolyte bilayers on the surface of the Pt / Ce02 / Nafion ™ composite coating and the PAH / SPEEK polyelectrolyte bilayers were not coated on the second surface of the enhanced Nafion ™ XL base membrane. The coated membrane was dried at 60 °C for 30 minutes to form a PEM-RHPE membrane.
[0064] Example 2: Manufacture of Catalyst Coated Proton Exchange Membrane (Abbreviated as PEM-RHPE-CCM) using PEM-RHPE Membrane
[0065] an additive solution including Ir02oxygen evolution reaction (OER) catalyst, water, poly(3,4-ethylenedioxythiophene) (PEDOT), EtOH, and Nafion ™ anode ink was coated on the surface of the PAH / SPEEK polyelectrolyte bilayers of the PEM-RHPE membrane. After anode coating, the anode catalyst-coated membrane was dried at 60 °C for 30 minutes. The anode Ir02loading was 1.0 mg / cm 2 Then, an additive solution including Pt / C catalyst, water, PEDOT solution, EtOH, and Nafion ™Cathode ink of ionomer suspension was coated on the second surface of PEM-RHPE membrane to form a three-layer catalyst coated membrane (CCM) PEM-RHPE-CCM. The PEM-RHPE-CCM was dried at 60 °C for 30 minutes and then at 100 °C for another 2 hours. The cathode Pt loading was 0.2 mg / cm 2 The PEM-RHPE-CCM was soaked in 0.1 M H2SO4 at room temperature for 24 hours, rinsed with ultrapure water, and finally air dried at room temperature for 16 hours. After drying, the PEM-RHPE-CCM was hot pressed to form the final PEM-RHPE-CCM.
[0066] Comparative Example 1 : Using Nafion ™ 115 Catalyst-coated proton exchange membrane (abbreviated as N115-CCM)
[0067] An additive solution including IrO2 catalyst, water, poly(3,4- ethylenedioxythiophene) (PEDOT), EtOH, and Nafion ™ Anode ink of ionomer suspension was sprayed on one surface of Nafion ™ 115 membrane. The anode IrO2 loading was 1.0 mg / cm 2 Then, an additive solution including Pt / C catalyst, water, PEDOT solution, EtOH, and Nafion ™ Cathode ink of ionomer suspension was sprayed on the second surface of Nafion ™ 115 membrane to form a three-layer catalyst coated membrane N115-CCM. The cathode Pt loading was 0.2 mg / cm 2 The N115-CCM was soaked in 0.1 M H2SO4 at room temperature for 24 hours, rinsed with ultrapure water, and finally air dried at room temperature for 16 hours.
[0068] Example 3: In-Plane H of PEM-RHPE Films + Conductivity Evaluation
[0069] The PEM-RHPE membrane prepared in Example 1 was cut into 1 cm wide strips and placed in a glass bottle. It was soaked in 1 M HC1 solution at 80 °C for 16 hours. The membrane was then soaked in ultrapure water to remove HC1 from the membrane. The membrane was rinsed with ultrapure water three times and then mounted in a test cell with three Pt electrodes and soaked in fresh ultrapure water at room temperature. The test cell was connected to a potentiostat (Gamry Reference 600+) (impedance analyzer for electrochemical impedance spectroscopy (EIS)). The constant current EIS measurement was taken in the range of 100 kHz to 10 Hz with 10 points per decade rate. The resistance was extracted from the Nyquist plot and the in-plane H + conductivity was calculated. The in-plane H +The conductivity was 116 mS / cm.
[0070] Example 4: Water Electrolysis Performance Evaluation of PEM-RHPE-CCM and N115-CCM
[0071] The water electrolysis performance of the N115-CCM prepared in Comparative Example 1 and the PEM-RHPE-CCM prepared in Example 2 was evaluated in a Scribner setup at atmospheric pressure using a single water electrolyzer. The CCMs were sandwiched between carbon paper and Pt-coated titanium porous transport layers (PTLs) to form catalyst-coated membrane electrode assemblies. The catalyst-coated membrane electrode assemblies were then installed in a Scribner test cell with an active catalyst-coated area of 5 cm 2 The water electrolysis performance of the N115-CCM prepared in Comparative Example 1 and the PEM-RHPE-CCM prepared in Example 2 was evaluated in a Scribner setup at atmospheric pressure using a single water electrolyzer. The CCMs were sandwiched between carbon paper and Pt-coated titanium porous transport layers (PTLs) to form catalyst-coated membrane electrode assemblies. The catalyst-coated membrane electrode assemblies were then installed in a Scribner test cell with an active catalyst-coated area of 5 cm 2 The water electrolysis performance of the N115-CCM prepared in Comparative Example 1 and the PEM-RHPE-CCM prepared in Example 2 was evaluated in a Scribner setup at atmospheric pressure using a single water electrolyzer. The CCMs were sandwiched between carbon paper and Pt-coated titanium porous transport layers (PTLs) to form catalyst-coated membrane electrode assemblies. The catalyst-coated membrane electrode assemblies were then installed in a Scribner test cell with an active catalyst-coated area of 5 cm Figure 5 The PEM-RHPE-CCM was observed to exhibit a much higher current density than the N115-CCM at 1.7 V cell voltage from the polarization curves in Table 5, indicating that a water electrolyzer comprising the PEM-RHPE-CCM has a higher hydrogen production rate than a water electrolyzer comprising the N115-CCM. In addition, the PEM-RHPE-CCM exhibited lower H2 crossover than the N115-CCM. At a current density of 2 A / cm 2 The PEM-RHPE-CCM exhibited a H2 concentration in O2 in the anode gas stream as low as 0.06% at a current density of 2 A / cm 2 The PEM-RHPE-CCM exhibited a H2 concentration in O2 in the anode gas stream as low as 0.06% at a current density of 2 A / cm
[0072] Specific Embodiments
[0073] While the following is described in conjunction with the specific embodiments, it will be understood that it is intended to cover not only the descriptions but also the examples and the following claims.
[0074] A first embodiment of the invention is a composition comprising: a reinforcing membrane having a first surface and a second surface, the reinforcing membrane having a thickness less than or equal to 100 pm; a continuous non-porous hydrogen recombiner catalyst coating having a first surface and a second surface, the first surface of the continuous non-porous hydrogen recombiner catalyst coating on the first surface of the reinforcing membrane, the continuous non-porous hydrogen recombiner catalyst coating comprising a mixture of a hydrogen recombiner catalyst and a proton-conducting ionomer; and a continuous non-porous crosslinked polyelectrolyte multilayer coating on the second surface of the continuous non-porous hydrogen recombiner catalyst coating, the non-porous crosslinked polyelectrolyte multilayer coating comprising alternating layers of a polycationic polymer and a poly anionic polymer, and wherein a polycationic polymer layer is in contact with the continuous non-porous hydrogen recombiner catalyst coating. One embodiment of the invention is any one or all of the previous embodiments in this paragraph through the first embodiment of this paragraph, wherein the reinforcing membrane comprises a single layer membrane comprising a first reinforcing material and a first proton-conducting ionomer or a multi-layer membrane comprising at least one reinforcing layer and at least one non-reinforcing layer, wherein the at least one reinforcing layer comprises a second reinforcing material and a second proton-conducting ionomer and the at least one non-reinforcing layer comprises a third proton-conducting ionomer.One embodiment of the application is any one, any combination of the preceding embodiments in this paragraph through the first embodiment of this paragraph, wherein the first proton-conducting ionomer, or the second proton-conducting ionomer, or the third proton-conducting ionomer, or a combination thereof, comprises a perfluorosulfonic acid (PFSA) polymer selected from the group consisting of a copolymer of tetrafluoroethylene and perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-5-oxa-6-heptene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-4-oxa-5-hexene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-3-oxa-4-pentene-sulfonic acid, a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2- methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2-methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2-methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2-methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and 2,2,4-trifluoro-5- trifluoromethoxy-l,3-dioxolene, a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and 2,2,4- trifluoro-5-trifluoromethoxy-l,3-dioxolene, a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-l,3-dioxolene, or a copolymer of perfluoro-3-oxa-4-pentene- sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-l,3-dioxolene, a non-PFSA polymer selected from the group consisting of sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(ether sulfone), sulfonated poly(phenyl sulfone), sulfonated poly(2,6-dimethyl-l,4-phenylene oxide), sulfonated poly(4- phenoxybenzoyl-l,4-phenylene), sulfonated poly(phenylene oxide), sulfonated poly(phenylene), sulfonated poly(phthalazinone), crosslinked SPEEK, crosslinked sulfonated poly(ether sulfone), crosslinked sulfonated poly(phenyl sulfone), crosslinked poly(phenylene sulfide sulfone nitrile), sulfonated polystyrene, sulfonated poly(vinyltoluene), crosslinked sulfonated polystyrene, or crosslinked sulfonated poly(vinyltoluene), or a combination thereof.One embodiment of the application is any one of or all of the preceding embodiments in this paragraph through the first embodiment of this paragraph, wherein the first reinforcing material or the second reinforcing material or both comprise polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), polyether ether ketone (PEEK), polyimide (PI), polyetherimide (PEI), polybenzoxazole (PBO), polybenzimidazole (PBI), polysulfone (PSF), polyethersulfone (PES), aromatic polyamide, polypropylene (PP), polyethylene (PE), co-PP-PE, or combinations thereof. One embodiment of the application is any one of or all of the preceding embodiments in this paragraph through the first embodiment of this paragraph, wherein the thickness of the reinforcing film is in the range of 10 pm to 90 pm. One embodiment of the application is any one of or all of the preceding embodiments in this paragraph through the first embodiment of this paragraph, wherein the hydrogen recombination catalyst comprises Pt, Pt supported on carbon or silica, PtCo, PtCo supported on carbon or silica, Pd, Pd supported on carbon or silica, PdCo, PdCo supported on carbon or silica, or mixtures thereof.One embodiment of the present application is one, any or all of the preceding embodiments in this paragraph through the first embodiment of this paragraph, wherein the proton-conducting ionomer in the continuous non-porous hydrogen recombination catalyst coating comprises a perfluorosulfonic acid (PFSA) polymer selected from the group consisting of a copolymer of tetrafluoroethylene and perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-5-oxa-6-heptene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-4-oxa-5-hexene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-3-oxa-4-pentene-sulfonic acid, a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2,2-dimethyl-1,3-dioxolene), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2,2-dimethyl-1,3-dioxolene), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2,2-dimethyl-1,3-dioxolene), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2,2-dimethyl-1,3-dioxolene), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxolene, a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxolene, a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxolene, or a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxolene, a non-PFSA polymer selected from the group consisting of sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(ether sulfone), sulfonated poly(phenyl sulfone), sulfonated poly(2,6-dimethyl-1,4-phenylene oxide), sulfonated poly(4-phenoxybenzoyl-1,4-phenylene), sulfonated poly(phenylene oxide), sulfonated poly(phenylene), sulfonated poly(phthalazinone), crosslinked SPEEK, crosslinked sulfonated poly(ether sulfone), crosslinked sulfonated poly(phenyl sulfone), crosslinked poly(phenylene sulfide sulfone nitrile), sulfonated polystyrene, sulfonated poly(vinyltoluene), crosslinked sulfonated polystyrene, or crosslinked sulfonated poly(vinyltoluene), or a combination thereof.One embodiment of the application is one, any or all of the previous embodiments in this paragraph through the first embodiment in this paragraph, wherein the continuous nonporous hydrogen recombination catalyst coating further comprises a radical scavenger. One embodiment of the application is one, any or all of the previous embodiments in this paragraph through the first embodiment in this paragraph, wherein the radical scavenger comprises Ce02, Ce(OH)4, Ce02 / Zr02, Ce(OH)4 / Zr02, or mixtures thereof. One embodiment of the application is one, any or all of the previous embodiments in this paragraph through the first embodiment in this paragraph, further comprising a second continuous nonporous polyelectrolyte multilayer coating on the second surface of the reinforcing membrane. One embodiment of the application is one, any or all of the previous embodiments in this paragraph through the first embodiment in this paragraph, wherein the continuous nonporous crosslinked polyelectrolyte multilayer coating comprises at least two sets of alternating layers of the polycationic polymer and the polyanionic polymer. One embodiment of the application is one, any or all of the previous embodiments in this paragraph through the first embodiment in this paragraph, wherein the ratio of the proton-conducting ionomer to the hydrogen recombination catalyst is in the range of 5001 to 201.
[0075] A second embodiment of the application is an apparatus comprising a proton exchange membrane comprising; a reinforcing membrane having a first surface and a second surface, the reinforcing membrane having a thickness less than or equal to 100 pm; a continuous nonporous hydrogen recombination catalyst coating having a first surface and a second surface, the first surface of the continuous nonporous hydrogen recombination catalyst coating on the first surface of the reinforcing membrane, the continuous nonporous hydrogen recombination catalyst coating comprising a mixture of a recombination catalyst and a proton-conducting ionomer; and a continuous nonporous crosslinked polyelectrolyte multilayer coating on the second surface of the continuous nonporous hydrogen recombination catalyst coating, the nonporous crosslinked polyelectrolyte multilayer coating comprising alternating layers of a polycationic polymer and a polyanionic polymer, and wherein the polycationic polymer layers are in contact with the continuous nonporous hydrogen recombination catalyst coating; an anode on a second surface of the continuous nonporous crosslinked polyelectrolyte multilayer coating; and a cathode on the second surface of the reinforcing membrane; or a cathode on a second surface of a second continuous nonporous polyelectrolyte multilayer coating on the second surface of the reinforcing membrane.
[0076] A third embodiment of the present invention is a method of making a proton exchange membrane, the method comprising: directly applying a continuous non-porous hydrogen recombiner catalyst coating on a first surface of a reinforced membrane, the continuous non-porous hydrogen recombiner catalyst coating comprising a mixture of a recombiner catalyst and a proton-conducting ionomer, the reinforced membrane having a thickness less than or equal to 100 pm; and directly applying a continuous non-porous crosslinked polyelectrolyte multilayer coating on a surface of the continuous non-porous hydrogen recombiner catalyst coating, the continuous non-porous crosslinked polyelectrolyte multilayer coating comprising alternating layers of a polycationic polymer and a poly anionic polymer, wherein the polycationic polymer layer is in contact with the continuous non-porous hydrogen recombiner catalyst coating. One embodiment of the present invention is one, any or all of the preceding embodiments in this paragraph through the third embodiment of this paragraph, wherein the reinforced membrane is a single layer membrane comprising a first reinforcing material and a first proton-conducting ionomer or a multi-layer membrane comprising at least one reinforced membrane layer and at least one unreinforced membrane layer, wherein the at least one reinforced membrane layer comprises a second reinforcing material and a second proton-conducting ionomer and the at least one unreinforced membrane layer comprises a third proton-conducting ionomer. One embodiment of the present invention is one, any or all of the preceding embodiments in this paragraph through the third embodiment of this paragraph, wherein the continuous non-porous hydrogen recombiner catalyst coating further comprises a radical scavenger comprising Ce02, Ce(OH)4, Ce02 / Zr02, Ce(OH)4 / Zr02, or a mixture thereof. One embodiment of the present invention is one, any or all of the preceding embodiments in this paragraph through the third embodiment of this paragraph, further comprising: directly applying an anode on a second surface of the continuous non-porous crosslinked polyelectrolyte multilayer coating; and directly applying a cathode to a second surface of the reinforced membrane.One embodiment of the application is any one of the previous embodiments in this paragraph through the third embodiment of this paragraph, wherein the first proton-conducting ionomer, or the second proton-conducting ionomer, or the third proton-conducting ionomer, or a combination thereof, comprises a perfluorosulfonic acid (PFSA) polymer selected from the group consisting of a copolymer of tetrafluoroethylene and perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-5-oxa-6-heptene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-4-oxa-5-hexene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-3-oxa-4-pentene-sulfonic acid, a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2,2-dimethyl-l,3- dioxolene), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2- methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2-methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2-methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2-methylene-4-methyl-l,3-dioxolane), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and 2,2,4-trifluoro-5- trifluoromethoxy-l,3-dioxolene, a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and 2,2,4- trifluoro-5-trifluoromethoxy-l,3-dioxolene, a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-l,3-dioxolene, or a copolymer of perfluoro-3-oxa-4-pentene- sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-l,3-dioxolene, a non-PFSA polymer selected from the group consisting of sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(ether sulfone), sulfonated poly(phenyl sulfone), sulfonated poly(2,6-dimethyl-l,4-phenylene oxide), sulfonated poly(4- phenoxybenzoyl-l,4-phenylene), sulfonated poly(phenylene oxide), sulfonated poly(phenylene), sulfonated poly(phthalazinone), crosslinked SPEEK, crosslinked sulfonated poly(ether sulfone), crosslinked sulfonated poly(phenyl sulfone), crosslinked poly(phenylene sulfide sulfone nitrile), sulfonated polystyrene, sulfonated poly(vinyltoluene), crosslinked sulfonated polystyrene, or crosslinked sulfonated poly(vinyltoluene), or a combination thereof.One embodiment of the application is any one of the preceding embodiments in this paragraph through any one of the third embodiments of this paragraph, wherein the first reinforcing material or the second reinforcing material, or both, comprises polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), polyether ether ketone (PEEK), polyimide (PI), polyetherimide (PEI), polybenzoxazole (PBO), polybenzimidazole (PBI), polysulfone (PSF), polyethersulfone (PES), aramid, polypropylene (PP), polyethylene (PE), co-PP-PE, or a combination thereof.One embodiment of the application is one, any or all of the preceding embodiments in this paragraph through the third embodiment of this paragraph, wherein the proton-conducting ionomer in the continuous non-porous hydrogen recombination catalyst coating comprises a perfluorosulfonic acid (PFSA) polymer selected from the group consisting of a copolymer of tetrafluoroethylene and perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-5-oxa-6-heptene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-4-oxa-5-hexene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-3-oxa-4-pentene-sulfonic acid, a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2,2-dimethyl-1,3- dioxolene), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2,2-dimethyl-1,3- dioxolene), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2,2-dimethyl-1,3- dioxolene), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2,2-dimethyl-1,3- dioxolene), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2- methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and 2,2,4-trifluoro-5- trifluoromethoxy-1,3-dioxolene, a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and 2,2,4- trifluoro-5-trifluoromethoxy-1,3-dioxolene, a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxolene, or a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxolene, a non-PFSA polymer selected from the group consisting of sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(ether sulfone), sulfonated poly(phenyl sulfone), sulfonated poly(2,6-dimethyl-1,4- phenylene oxide), sulfonated poly(4-phenoxybenzoyl-1,4-phenylene), sulfonated poly(phenylene oxide), sulfonated poly(phenylene), sulfonated poly(phthalazinone), crosslinked SPEEK, crosslinked sulfonated poly(ether sulfone), crosslinked sulfonated poly(phenyl sulfone), crosslinked poly(thio- phenylene sulfone nitrile), sulfonated polystyrene, sulfonated poly(vinyltoluene), crosslinked sulfonated polystyrene, or crosslinked sulfonated poly(vinyltoluene), or a combination thereof.
[0077] While the foregoing description has been made in the context of particular embodiments, it should be recognized that those skilled in the art, in light of this description, will be able to utilize the application to its fullest extent and will be able to make variations and modifications without departing from the spirit and scope of the application. Therefore, the foregoing preferred specific embodiments are to be construed as merely illustrative, and not limiting of the remainder of the disclosure in any way whatsoever, and it is intended to cover all modifications and equivalents within the scope of the appended claims.
[0078] In the foregoing, all temperatures are presented in degrees Celsius and all parts and percentages are by weight unless otherwise indicated.
Claims
1. A proton exchange membrane (305), comprising: a reinforced membrane (310) having a first surface and a second surface, the reinforced membrane (310) having a thickness less than or equal to 100 pm; a continuous non-porous hydrogen recombination catalyst coating (325) having a first surface and a second surface, the first surface of the continuous non-porous hydrogen recombination catalyst coating (325) on the first surface of the reinforced membrane (310), the continuous non-porous hydrogen recombination catalyst coating (325) comprising a mixture of a hydrogen recombination catalyst (330) and a proton-conducting ionomer (335); and a continuous non-porous crosslinked polyelectrolyte multilayer coating (340) on the second surface of the continuous non-porous hydrogen recombination catalyst coating (325), the non-porous crosslinked polyelectrolyte multilayer coating (340) comprising alternating layers of a polycationic polymer and a poly anionic polymer, and wherein a polycationic polymer layer is in contact with the continuous non-porous hydrogen recombination catalyst coating (325).
2. The proton exchange membrane of claim 1, wherein the reinforced membrane (310) comprises a single layer membrane comprising a first reinforcing material (315) and a first proton-conducting ionomer (320), or a multi-layer membrane (401) comprising at least one reinforcing layer (420) and at least one non-reinforced layer (460), wherein the at least one reinforcing layer (420) comprises a second reinforcing material (415) and a second proton-conducting ionomer (410), and the at least one non-reinforced layer (460) comprises a third proton-conducting ionomer.
3. The proton exchange membrane of claim 2, wherein the first proton conducting ionomer (320) or the second proton conducting ionomer (410) or the third proton conducting ionomer or a combination thereof comprises a perfluorosulfonic acid (PFSA) polymer selected from a copolymer of tetrafluoroethylene and perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-5-oxa-6-heptene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-4-oxa-5-hexene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-3-oxa-4-pentene-sulfonic acid, a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2,2-dimethyl-1,3- dioxolene), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2,2-dimethyl- 1,3-dioxolene), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2,2-dimethyl- 1,3-dioxolene), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2,2-dimethyl- 1,3-dioxolene), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2- methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-4-oxa-5-hexene- sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-3-oxa- 4-pentene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and 2,2,4-trifluoro-5- trifluoromethoxy-1,3-dioxolene, a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxolene, a copolymer of perfluoro-4-oxa-5-hexene- sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxolene, or a copolymer of perfluoro- 3-oxa-4-pentene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxolene, a non-PFSA polymer selected from sulfonated poly(ether ether ketone) (SPEEK), sulfonated polyether sulfone, sulfonated polyphenyl sulfone, sulfonated poly(2,6-dimethyl-1,4- phenylene oxide), sulfonated poly(4-phenoxybenzoyl-1,4-phenylene), sulfonated polyphenylene oxide, sulfonated poly(phenylene), sulfonated poly(phthalazinone), crosslinked SPEEK, crosslinked sulfonated polyether sulfone, crosslinked sulfonated polyphenyl sulfone, crosslinked poly(phenylene sulfide sulfone nitrile), sulfonated polystyrene, sulfonated poly(vinyltoluene), crosslinked sulfonated polystyrene, or crosslinked sulfonated poly(vinyltoluene), or a combination thereof.
4. The proton exchange membrane of claim 2, wherein the first reinforcing material (315) or the second reinforcing material (415) or both comprise polytetrafluoroethylene (PTFE), polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), polyether ether ketone (PEEK), polyimide (PI), polyetherimide (PEI), polybenzoxazole (PBO), polybenzimidazole (PBI), polysulfone (PSF), polyethersulfone (PES), aramid, polypropylene (PP), polyethylene (PE), co-PP-PE, or combinations thereof.
5. The proton exchange membrane of any one of claims 1-2, wherein the hydrogen gas reforming catalyst (330) comprises Pt, Pt supported on carbon or silica, PtCo, PtCo supported on carbon or silica, Pd, Pd supported on carbon or silica, PdCo, PdCo supported on carbon or silica, or mixtures thereof.
6. The proton exchange membrane of any one of claims 1 to 2, wherein the proton-conducting ionomer (335) in the continuous, non-porous hydrogen recombination catalyst coating (325) comprises a perfluorosulfonic acid (PFSA) polymer selected from a copolymer of tetrafluoroethylene and perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-5-oxa-6-heptene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-4-oxa-5-hexene-sulfonic acid, a copolymer of tetrafluoroethylene and perfluoro-3-oxa-4-pentene-sulfonic acid, a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2,2-dimethyl-1,3- dioxolene), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2,2-dimethyl-1,3- dioxolene), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2,2-dimethyl-1,3- dioxolene), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2,2-dimethyl-1,3- dioxolene), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and perfluoro(2- methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-3-oxa-4-pentene-sulfonic acid and perfluoro(2-methylene-4-methyl-1,3-dioxolane), a copolymer of perfluoro-3,6-dioxa-4-methyl-7-octene-sulfonic acid and 2,2,4-trifluoro-5- trifluoromethoxy-1,3-dioxolene, a copolymer of perfluoro-5-oxa-6-heptene-sulfonic acid and 2,2,4- trifluoro-5-trifluoromethoxy-1,3-dioxolene, a copolymer of perfluoro-4-oxa-5-hexene-sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxolene, or a copolymer of perfluoro-3-oxa-4-pentene- sulfonic acid and 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxolene, a non-PFSA polymer selected from sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(ether sulfone), sulfonated poly(phenyl sulfone), sulfonated poly(2,6-dimethyl-1,4-phenylene oxide), sulfonated poly(4-phenoxybenzoyl-1,4- phenylene), sulfonated poly(phenylene oxide), sulfonated poly(phenylene), sulfonated poly(phthalazinone), crosslinked SPEEK, crosslinked sulfonated poly(ether sulfone), crosslinked sulfonated poly(phenyl sulfone), crosslinked poly(phenylene sulfide sulfone nitrile), sulfonated polystyrene, sulfonated poly(vinyltoluene), crosslinked sulfonated polystyrene, or crosslinked sulfonated poly(vinyltoluene), or a combination thereof.
7. The proton exchange membrane of any one of claims 1-2, wherein the continuous non- porous hydrogen recombination catalyst coating (325) further comprises a radical scavenger, and wherein the radical scavenger comprises Ce02, Ce(OH)4, Ce02 / Zr02, Ce(OH)4 / Zr02, or a mixture thereof.
8. The proton exchange membrane of any one of claims 1-2, further comprising a second continuous non-porous polyelectrolyte multilayer coating (345) on the second surface of the reinforced membrane (310).
9. The proton exchange membrane of any one of claims 1-2, wherein the continuous non- porous crosslinked polyelectrolyte multilayer coating (340) comprises at least two sets of alternating layers of the polycationic polymer and the polyanionic polymer.
10. A method of making a proton exchange membrane, the method comprising: applying a continuous non-porous hydrogen recombination catalyst coating (325) directly on a first surface of a reinforced membrane (310), the continuous non-porous hydrogen recombination catalyst coating (325) comprising a mixture of a recombination catalyst (330) and a proton-conducting ionomer (335), the reinforced membrane (310) having a thickness less than or equal to 100 pm, wherein the reinforced membrane (310) is a single layer membrane comprising a first reinforcing material (315) and a first proton-conducting ionomer (320), or a multi-layer membrane (401) comprising at least one reinforced layer (420) and at least one unreinforced layer (460), wherein the at least one reinforced layer (420) comprises a second reinforcing material (415) and a second proton-conducting ionomer (410), and the at least one unreinforced layer (460) comprises a third proton-conducting ionomer; and applying a continuous non-porous crosslinked polyelectrolyte multilayer coating (340) directly on a surface of the continuous non-porous hydrogen recombination catalyst coating (325), the continuous non-porous crosslinked polyelectrolyte multilayer coating (340) comprising alternating layers of a polycationic polymer and a polyanionic polymer, wherein the polycationic polymer layers are in contact with the continuous non-porous hydrogen recombination catalyst coating (325); optionally applying an anode (350) directly on a second surface of the continuous non- porous crosslinked polyelectrolyte multilayer coating (340); and applying a cathode (355) directly to a second surface of the reinforced proton exchange membrane layer (310); or optionally applying an anode (350) directly on a second surface of the continuous non- porous crosslinked polyelectrolyte multilayer coating (340); applying a second continuous non- porous crosslinked polyelectrolyte multilayer coating directly on a second surface of the reinforced proton exchange membrane layer (310); and applying a cathode (355) directly to a second surface of the second continuous non-porous crosslinked polyelectrolyte multilayer coating (340).
Citation Information
Patent Citations
Composite proton conductive membranes
US11970589B2
Cited By
Cationic COF-doped AEM electrode and preparation method and application thereof
CN121951586A